CLASSIFICATION OF ENLISTED AYURVEDIC LIPID LOWERING HERBS ACCORDING TO PRINCIPLE OF AYURVEDA - Borkar, Sunil; S.K.Jaiswal, (International Journal of Ayurveda and Pharma Research, 2019)
INTRODUCTION: Dyslipidemia is a condition marked by unhealthy abnormal concentrations of lipids in blood. There is no direct description of dyslipidemia in Ayurvedic texts. However Medo Rogas (Fat disorders) are described in Ayurvedic texts since ancient times. Dyslipidemia (Medo roga) is a disease of diminished Jatharagni, Bhutagni and Dhatwagni induced apachita or saam asthayi meda dhatu vriddhi. So for the management of Dyslipidemia (Medo roga) such drugs are needed which having Deepan, Pachan, Kaphaghna and Medoghna properties. In this regards it is time essential to classify them by considering its specific therapeutic effect and not only by using as a indistinct lipid lowering agent. AIM: To review the properties and action of Ayurvedic lipid lowering herbs against specific involved samprapti ghatak (Pathological factor) in the management of Dyslipidemia (Medo roga).  RESULT: Study provides good evidence of classification of Ayurvedic lipid lowering herbs in the management of Dyslipidemia (Medo roga).